A theory of latticed plates and shells - Pshenichnov, G. I. (World Scientific, 1993)
The book presents the theory of latticed shells as continual systems and describes its applications. It analyses the problems of statics, stability and dynamics. Generally, a classical rod deformation theory is applied. However, in some instances, more precise theories which particularly consider geometrical and physical nonlinearity are employed. A new effective method for solving general boundary value problems and its application for numerical and analytical solutions of mathematical physics and reticulated shell theory problems is described. A new method of solving the shell theory's nonlinear problems, substantially simplifying the existing algorithms is given. Questions of optimum design are discussed. Some of the findings are generalized and extended to edged and composite systems. The results of the solutions of a wide range of pressing problems are presented.
Keywords: Elastic plates and shells.; elektronické knihy; electronic books